Gender, sexuality and colonial modernities - Burton, Antoinette M. (Routledge research in gender and history, 1999)
Gender, Sexuality and Colonial Modernities considers the ways in which modernity was constructed, in all its incompleteness, through colonialism. Using a variety of archival resources and equally diverse methodologies, the authors trace modernity's unstable foundations in the slippages and ruptures of colonial gender and sexual politics. As a whole, the essays illustrate that modern colonial regimes are never self-evidently hegemonic, but are always in process - subject to disruption and contest - and never finally accomplished; and are therefore unfinished business.
Keywords: 1800-1899; approches et analyses; colonialisme; cours; discipline; europe; fem1000; féminisme décolonial; histoire; occident; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; époque moderne; études postcoloniales

Postcolonial subjects: Francophone women writers - Green, Mary (University of Minnesota Press, 1996)
Sujets postcoloniaux » est un projet collectif centré sur les questions de langue, d'identité et de voix alors qu'ils abordent les questions de genre, de race, d'ethnicité, de culture et de nation. Les essais critiques présentés ici portent sur les contributions littéraires de femmes contemporaines écrivant en français dont les liens culturels, les identités ethniques et les racines historiques se situent au-delà de l'Hexagone, au-delà de la carte à six faces de la France.
Keywords: approches et analyses; cours; discipline; europe; fem1000; france; francophonie; féminisme décolonial; littérature; premier cycle; ressource en ligne; régions géographiques; thématiques; écriture des femmes*; études littéraires